Applying Suggestibility Research to the Real World: The Case of Repeated Questions - Lyon, Thomas D. (2002)
One can discern two parallel trends in the law and the psychology of child witnesses. In the law, appellate courts are beginning to stem the once powerful movement to increase the acceptance of children's testimony and the admissibility of children's out-of-court statements. Lyon analyzes particular strands of each trend